Evolution of the Amorphous Phase of the Alloy Co67Nb25B17 - Nascimento, Luciano (Orbital: The Electronic Journal of Chemistry, 2021)
The purpose of this work is to elaborate the amorphous alloy compound Co67Nb25B17 from elementary powders using the planetary ball. The grinding of the amorphous Co67Nb25B17 alloy was carried out for grinding times of 1, 5, 10 and 15 h. In 15 hours, the desired amorphous phase was obtained. The microstructural evolution was followed by the techniques of X-Ray Diffraction (XRD), Scanning Electron Microscopy and Energy Dispersion Spectroscopy (SEM / EDS). Experimental results show that the evolution of the amorphous phase was rapid at a speed of 300 rpm. DOI: http://dx.doi.org/10.17807/orbital.v13i1.1586